Effect of per oral sipermetrin exposure on serum 17-beta estradiol and uterine malondialdehyde (MDA) levels in female Wistar strain rats (Rattus norvegicus) - Hesty Widowati; Hidayat Sujuti; Karyono Mintaroem (Universitas Airlangga, 2018)
Objective: This study aimed to verify the effect of oral siper-metrin exposure to decrease serum estradiol 17b levels and increased malondialdehyde (MDA) in the uterus level of female Wistar strain rats (Rattus norvegicus).Materials and Methods: The method of this study was true experimental post test only control group in vivo using 24 female rats, divided into 3 groups treated by administering a dose of 5, 10 and 20 mg/kg sipermetrin for 28 days and one control group. Then blood samples were taken from the heart for measurement of serum estradiol 17b levels by ELISA and uterine organs were taken for measurement of Malondialdehyde (MDA) with spectro-photometry method.Results: The results of the measurement of serum estradiol 17b and uterus malondialdehyde (MDA) levels of female Wistar strain rats (Rattus norvegicus) showed an opposite pattern, where there was a decline in serum estradiol 17b levels and an increase in uterus malondialdehyde (MDA) level. There was a significant difference (p=0.000<alpha) in 17b estradiol serum and uterus Malondialdehyde (MDA) levels of female rats between control group and group exposed to sipermetrin treatment for 28 days.Conclusions: Oral sipermetrin exposure can decrease serum levels of estradiol 17b and increase uterine levels of malondi-aldehyde (MDA) of female Wistar strain rats (Rattus norvegicus).